An automated approach for mapping inland valleys on suitability for rice production in Sub-Saharan Africa - CGIAR Research Program on Rice (2020)
The approach has been implemented using DEMs of Benin, Cote d’Ivoire, Ghana, and Togo. Areas that are suitable for rice cultivation was estimated for Benin and Togo.